A Suggested methodology for assessing and rehabilitation of damaged building - موسى, شذا; فايز جراد; علي خيربك (Latakia University Journal -Engineering Sciences Series, 2024)
The damaged building repairability evaluation process is considered a challenging process that requires significant experience from the evaluator. It also often depends on the opinions and judgment of the evaluators and varies according to their experiences in this field. Repairability evaluation of damaged buildings is considered a multi-criteria decision-making (MCDM) process. During this study, a set of criteria was presented derived from previous studies, expert opinions, and evaluation companies' reports to unify the evaluation process among evaluators and enable non-expert engineers or freshly graduated engineers to obtain Pleasant and reliable results without the need for expert opinions. Then, the weights of these criteria were calculated according to the Syrian reality through statistical analysis of the experts’ opinions using the AHP (Analytic hierarchy process) method to give weights to these criteria according to the local situation using Expert Choice program. These criteria have been programmed according to a computer program whose inputs are the building data collected according to the established criteria and whose outputs are the degree of damage to the building and its ability to be repaired. That aims to facilitate use, provide speed and accuracy for the evaluation process, and make the evaluation available to all engineers regardless of their experience so that they obtain the same result when they conduct the assessment. The suggested methodology and its programming according to the computer program make it easier to survey a larger area of damaged buildings and make a reliable determination of repairability. The validity and accuracy of the program were confirmed by studying four buildings (case studies). One was damaged by the earthquake-which will be mentioned in this article, and Three were Affected by the war. It has been proven through experience that the programs' outputs are consistent with the judgment of the expert engineers.